Inclusive production of charged pions in p+p collisions at 158 GeV/c beam momentum - Alt, C.; Antičić, Tome; Baatar, B. Barna, D.; Bartke, J. Betev, L.; Bialkowska, H. Blume, C.; Boimska, B. Botje, M.; Bracinik, J. Bunčić, P.; Cerny, V. Christakoglou, P.; Chvala, O. Dinkelaker, P.; Dolejsi, J. Eckardt, V.; Fischer, H.G. Flierl, D.; Fodor, Z. Foka, P.; et al. (2006)
New results on the production of charged pions in p+p interactions are presented. The data come from a sample of 4.8 million inelastic events obtained with the NA49 detector at the CERN SPS at 158 GeV/c beam momentum. Pions are identified by energy loss measurement in a large TPC tracking system which covers a major fraction of the production phase space. Inclusive invariant cross sections are given on a grid of nearly 300 bins per charge over intervals from 0 to 2 GeV/c in transverse momentum and from 0 to 0.85 in Feynman x. The results are compared to existing data in overlapping energy ranges.
Projekt MZOS
ENG